Interaction Between PEDV and Its Hosts: A Closer Look at the ORF3 Accessory Protein - Jantraphakorn, Yuparat; Viriyakitkosol, Ratchanont; Jongkaewwattana, Anan; Kaewborisuth, Challika (Frontiers in Veterinary Science, 2021)
Porcine epidemic diarrhea virus (PEDV) is a causative agent of a highly contagious enteric disease in swine of all ages, leading to severe economic losses for the swine industry in many countries. One of the most effective approaches in controlling PEDV infection is vaccination. The ORF3 accessory protein has been proposed as a crucial viral virulence factor in a natural host. However, due to the lack of an extensive comparative study of ORF3, exactly how the ORF3 takes part in virus replication and pathogenesis as well as its role in host-virus interaction is unclear. In this review, we aim to discuss the current knowledge of ORF3 concerning its dispensability for viral replication in vitro, ability to modulate host responses, contribution to virus pathogenicity, and research gaps among ORF3 functional studies. These will be beneficial for further studies to a better understanding of PEDV biology and PEDV vaccine development.